2022
DOI: 10.1111/ans.17669
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of interhospital transfer delays in acute surgical patient deaths in Australia: a retrospective study

Abstract: This paper is not based on any previous communications to a society or meeting. All authors had full access to all data, tables and statistical reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…A recent systematic review by Young et al revealed that there remains a general paucity of knowledge regarding the factors influencing IHT delays 32 . A retrospective cohort study demonstrated modifiable predictors of IHT delay were inadequate clinical assessment, poor communication and multiple transfers 18 , similar to the highlighted themes identified during this thematic analysis.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…A recent systematic review by Young et al revealed that there remains a general paucity of knowledge regarding the factors influencing IHT delays 32 . A retrospective cohort study demonstrated modifiable predictors of IHT delay were inadequate clinical assessment, poor communication and multiple transfers 18 , similar to the highlighted themes identified during this thematic analysis.…”
Section: Discussionsupporting
confidence: 65%
“…A 2010 Cochrane review identified clinical pathway documents that link up-to-date evidence with specific health conditions are associated with reduced in-hospital complications and improved documentation without negatively affecting duration of hospital stay or cost 17 . A recent analysis of IHT patients using ANZASM data found that inadequate clinical assessment resulted in a 49.5-fold increased likelihood of transfer delay 18 , resulting in poorer patient outcomes 4 . Finally, important clinical management issues were identified associated with insufficient monitoring and a delay in recognizing complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue of the journal includes three papers on the topic of inter‐hospital transfers. The first is a 20‐year retrospective study of over 8000 surgical cases that that underwent transfer and who subsequently died 2 . Given the study was based on the Australian and New Zealand audit of surgical mortality (ANZASM), it could not report on the much larger number of transferred patients who survive.…”
mentioning
confidence: 99%
“…The first is a 20-year retrospective study of over 8000 surgical cases that that underwent transfer and who subsequently died. 2 Given the study was based on the Australian and New Zealand audit of surgical mortality (ANZASM), it could not report on the much larger number of transferred patients who survive. However, the authors identified both unmodifiable (gender and comorbidities) and modifiable predictors of delay (inadequate clinical assessment, poor communication and multiple transfers) and whether any delay contributed to death.…”
mentioning
confidence: 99%